2020
DOI: 10.1111/ncn3.12366
|View full text |Cite
|
Sign up to set email alerts
|

Staging of tau distribution by positron emission tomography may be useful in clinical staging of Alzheimer disease

Abstract: Background Clinical staging of Alzheimer disease (AD) may help develop novel treatment in the early stage. Aim We measured the accumulation of amyloid beta (Aβ) and tau with positron emission tomography (PET) in patients with AD to explore its utility for clinical staging. Methods Six patients with AD, two patients with mild cognitive impairment (MCI), and 12 healthy controls (HC) were studied. Aβ and tau accumulation was evaluated with [11C]PiB and [11C]PBB3, respectively. Results PBB3‐PET showed that two cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
(67 reference statements)
1
11
1
Order By: Relevance
“…Previous clinical trials targeting accumulated Aβ were mostly successful in reducing Aβ but failed to improve the clinical outcomes and even worsened the outcomes in some studies [ 18 ]. In contrast, in the present and previous studies, we demonstrated that tau accumulates more widely as the disease progresses in SAD [ 15 ]. The burden of tau was also heavy in FAD (Osaka) without amyloid accumulation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous clinical trials targeting accumulated Aβ were mostly successful in reducing Aβ but failed to improve the clinical outcomes and even worsened the outcomes in some studies [ 18 ]. In contrast, in the present and previous studies, we demonstrated that tau accumulates more widely as the disease progresses in SAD [ 15 ]. The burden of tau was also heavy in FAD (Osaka) without amyloid accumulation.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously reported that in SAD, tau accumulation spreads from the parahippocampal gyrus to the cerebral cortex with advancing phases of AD, whereas Aβ distribution is already advanced in the clinically earliest stage [ 15 ]. Similar reports supporting our data have been recently published by Jack et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a case in the present study, Spitzer et al also reported a 35‐year‐old woman with HDLS whose tau levels in the cerebrospinal fluid were moderately elevated 22 . We previously reported that tau accumulation spreads with disease progression in a large series of Alzheimer's disease 6 . Further studies are warranted to confirm the current hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…Pathologically, the spheroids in HDLS contain abnormal proteins, such as phosphorylated neurofilament and amyloid precursor protein 3,4 . The accumulation and spread of abnormal proteins, including amyloid β, tau, and α‐synuclein, is currently considered a cardinal mechanism involved in the development of neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease 6,7 . A similar spreading mechanism may be involved in HDLS.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies using a limited number of patients indicated sensitive detection of tau pathology by 11 C-PBB3 in patients with AD, with evidence of association between 11 C-PBB3 uptake and disease progression [ 18 , 19 ]. The 11 C-PBB3 distribution among cognitively normal and AD groups could mirror the pathological staging [ 20 ]. It was reported that in contrast to a relatively low 11 C-PIB uptake in the hippocampus as a cortical association area in AD, 11 C-PBB3 provided a robust signal in this region [ 18 ].…”
Section: Introductionmentioning
confidence: 99%